A multicenter retrospective study of charcot‐marie‐tooth disease type 4B (CMT4B) associated with mutations in myotubularin‐related proteins (MTMRs). Issue 1 (27th May 2019) - Pareyson, Davide; Stojkovic, Tanya; Reilly, Mary M.; Leonard‐Louis, Sarah; Laurà, Matilde; Blake, Julian; Parman, Yesim; Battaloglu, Esra; Tazir, Meriem; Bellatache, Mounia; Bonello‐Palot, Nathalie; Lévy, Nicolas; et al.
Abstract : Objective: Charcot‐Marie‐Tooth (CMT) disease 4B1 and 4B2 (CMT4B1/B2) are characterized by recessive inheritance, early onset, severe course, slowed nerve conduction, and myelin outfoldings. CMT4B3 shows a more heterogeneous phenotype. All are associated with myotubularin‐related protein (MTMR) mutations. We conducted a multicenter, retrospective study to better characterize CMT4B. Methods: We collected clinical and genetic data from CMT4B subjects in 18 centers using a predefined minimal data set including Medical Research Council (MRC) scores of nine muscle pairs and CMT Neuropathy Score. Results: There were 50 patients, 21 of whom never reported before, carrying 44 mutations, of which 21 were novel and six representing novel disease associations of known rare variants. CMT4B1 patients had significantly more‐severe disease than CMT4B2, with earlier onset, more‐frequent motor milestones delay, wheelchair use, and respiratory involvement as well as worse MRC scores and motor CMT Examination Score components despite younger age at examination. Vocal cord involvement was common in both subtypes, whereas glaucoma occurred in CMT4B2 only. Nerve conduction velocities were similarly slowed in both subtypes. Regression analyses showed that disease severity is significantly associated with age in CMT4B1. Slopes are steeper for CMT4B1, indicating faster disease progression. Almost none of the mutations in the MTMR2 and MTMR13 genes, responsible for CMT4B1 and B2, respectively, influence the correlation between disease severity and age, in agreement with the hypothesis of a complete loss of function of MTMR2/13 proteins for such mutations. Interpretation: This is the largest CMT4B series ever reported, demonstrating that CMT4B1 is significantly more severe than CMT4B2, and allowing an estimate of prognosis. ANN NEUROL 2019